Radiographers' conceptualisation of trauma imaging in Gauteng, South Africa - Shabnam Wahid; Shantel Lewis; Yasmin Casmod (AOSIS, 2024)
Background: Radiographers form part of the healthcare team and are integral in the diagnosis and treatment of trauma patients. Additionally, they are required to provide their services to multiple departments within the hospital, including the emergency department. Healthcare workers who work with trauma patients experience changes in their psychological functioning. Therefore, diagnostic radiographers may have similar experiences; however, limited studies were found on radiographers' conceptualisation of trauma imaging. Aim: The aim of this study was to explore and describe radiographers' conceptualisation of trauma imaging. Setting: One-on-one in-depth interviews were conducted virtually with radiographers in both the private and public healthcare sectors in Gauteng, South Africa. Method: In this qualitative, explorative and descriptive study, 20 radiographers were interviewed virtually through Zoom or WhatsApp video calls or telephone interviews. Participants were asked a central question: 'What does trauma imaging mean to you?' Detailed notes were taken during the interviews, and interviews were audio-recorded. The data was transcribed and underwent thematic analysis. Trustworthiness and ethical principles were adhered to throughout the study. Results: Thematic analysis identified four themes: (1) COVID-19 pandemic; (2) road accidents; (3) gender-based violence (GBV); and (4) paediatric injuries that participants conceptualised as trauma imaging. Conclusion: Participants conceptualised trauma imaging as COVID-19, road accidents, GBV and paediatric patients. It was noted that participants' personal experiences were significant contributors to their meaning-making and responses to trauma imaging. Contribution: The study has contributed to the understanding of the conceptualisation of trauma imaging from the perspective of diagnostic radiographers.